Blend Hydrogel Microspheres of Carboxymethyl Chitosan and Gelatin for the Controlled Release of 5-Fluorouracil - Vanarchi Rajini Kanth; Praveen B. Kajjari; Priya M. Madalageri; Sakey Ravindra; Lata S. Manjeshwar; Tejraj M. Aminabhavi (MDPI AG, 2017)
Carboxymethyl chitosan (CMCS) was synthesized and blended with gelatin (GE) to prepare hydrogel microspheres by w/o emulsion cross-linking in the presence of glutaraldehyde (GA), which acted as a cross-linker. 5-Fluorouracil (5-FU) was encapsulated to investigate its controlled release (CR) characteristics in acidic (pH 1.2) and alkaline (pH 7.4) buffer media. The microspheres which formed were spherical in nature, with smooth surfaces, as judged by the scanning electron microscopy (SEM). Fourier transform infrared spectroscopy (FTIR) confirmed the carboxymethylation of CS and the chemical stability of 5-FU in the formulations. Differential scanning calorimetry (DSC) and X-ray diffraction (XRD) confirmed the physical state and molecular level dispersion of 5-FU. Equilibrium swelling of microspheres was performed in water, in order to understand the water uptake properties. The in vitro release of 5-FU was extended up to 12 h in pH 7.4 phosphate buffer, revealing an encapsulation efficiency of 72%. The effects of blend composition, the extent of cross-linking, and initial drug loading on the in vitro release properties, were investigated. When analyzed through empirical equations, the release data suggested a non-Fickian transport mechanism.